2015
DOI: 10.1007/s13337-014-0246-4
|View full text |Cite
|
Sign up to set email alerts
|

First genome analysis and molecular characterization of Chickpea chlorotic dwarf virus Egyptian isolate infecting squash

Abstract: This study aims to identifying and characterizing some molecular properties of geminiviruses co-infection in squash field crop cultivated in Egypt. Squash crops observed to be heavily infected with several insect vectors, also severe chlorosis and stunting was observed. Electron microscopic analysis has revealed geminate capsid particles which indicate the infection of Geminiviruses, especially SqLCV which represent an economic problem to squash filed crop in Egypt. We have investigated possible mixed infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Thus, chickpea plays an important role in sustaining cereal based cropping system, which is the lifeline for food security in the country. The major constraints for the realization of the potential yield of chickpea are various diseases such as Fusarium wilt, root rot, Ascochyta blight, Botrytis grey mould, insect pest pod borer (Helicoverpa) and abiotic stresses namely terminal drought, high temperature during reproductive stage and cold sensitivity during the vegetative and flowering stages (Fahmy et al, 2015;Madrid et al, 2014;Varshney and Thudi, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, chickpea plays an important role in sustaining cereal based cropping system, which is the lifeline for food security in the country. The major constraints for the realization of the potential yield of chickpea are various diseases such as Fusarium wilt, root rot, Ascochyta blight, Botrytis grey mould, insect pest pod borer (Helicoverpa) and abiotic stresses namely terminal drought, high temperature during reproductive stage and cold sensitivity during the vegetative and flowering stages (Fahmy et al, 2015;Madrid et al, 2014;Varshney and Thudi, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Cajanus cajan , Dolichus lablab , Rinchosia minima ) in Sudan [ 5 ]; CpCDV was also detected in Beta vulgaris in Iran [ 6 ], in papaya ( Carica papaya ) in Burkina Faso [ 7 ], in some economically important Solanaceae such as pepper ( Capsicum annuum ) in Oman [ 8 ], and tomato ( Lycopersicon esculentum ) in Pakistan and Burkina Faso [ 7 , 9 ], in Malvaceae as okra ( Abelmoschus esculentus ) in Pakistan [ 10 ], and cotton ( Gossypium hirsutum ) in India [ 11 ]. CpCDV infects also other cucurbits beside watermelon [ 2 ], including squash ( Cucurbita pepo ) in Egypt [ 12 ] and cucumber ( Cucumis sativus ) in Pakistan [ 13 ]. CpCDV, as with other geminiviruses, is considered to be a dangerous emerging virus, with a high potential of recombination and spread in new areas infecting new crops [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although by exchanging/interchanging CP genes tween two divergent genera of geminiviridae leading to a transition in vector species from whitefly to leafhopper (Briddon et al, 1990). Recently, Fahmy et al (2015) reported a coinfection of CpCDV-CLCuBuV in a non-host species of dicot infecting mastrevirus i.e, squash. Full length complete genome of the CpCDV reported first time infecting squash in Egypt with its supposed recombination events beside molecular characterization and phylogenetic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…But in these reports the host is different every time belonging to different plant families. Mubin et al (2012) reported this mastrebegomo coinfection in weed (Family: Asteraceae) whereas Manzoor et al (2014) and Fahmy et al (2015) affirmed in cotton (Family: Malvaceae) and squash (Family: Cucurbitaceae), respectively. So, in order to investigate this aforesaid feature, we planned an experiment to remove coat protein (CP) gene of CpCDV (Genus: Mastrevirus) and in place of it insert the CP gene of CLCuBuV (Genus: Begomovirus) in order to make 'MastreBegomo chimera (Both viruses belonging to the same family Geminiviridae).…”
Section: Introductionmentioning
confidence: 95%